Van der Waals engineering of ferromagnetic semiconductor heterostructures for spin and valleytronics - Zhong, Ding; Seyler, Kyle L.; Linpeng, Xiayu; Cheng, Ran; Sivadas, Nikhil; Huang, Bevin; Schmidgall, Emma; Taniguchi, Takashi; Watanabe, Kenji; McGuire, Michael A.; Yao, Wang; Xiao, Di; et al. (Science advances, 2017)
A van der Waals heterostructure of monolayer WSe 2 and ferromagnetic CrI 3 enables exceptional control of valley pseudospin. The integration of magnetic material with semiconductors has been fertile ground for fundamental science as well as of great practical interest toward the seamless integration of information processing and storage. We create van der Waals heterostructures formed by an ultrathin ferromagnetic semiconductor CrI 3 and a monolayer of WSe 2 . We observe unprecedented control of the spin and valley pseudospin in WSe 2 , where we detect a large magnetic exchange field of nearly 13 T and rapid switching of the WSe 2 valley splitting and polarization via flipping of the CrI 3 magnetization. The WSe 2 photoluminescence intensity strongly depends on the relative alignment between photoexcited spins in WSe 2 and the CrI 3 magnetization, because of ultrafast spin-dependent charge hopping across the heterostructure interface. The photoluminescence detection of valley pseudospin provides a simple and sensitive method to probe the intriguing domain dynamics in the ultrathin magnet, as well as the rich spin interactions within the heterostructure.